Pontos de carbono obtidos da para-fenilenodiamina como sensores químicos: avaliação para cromo (III) em suplemento alimentar - Monteiro, Thyago Marques (2019)
In present work, we developed luminescent carbon dots for the analytical determination of chromium(III) in food supplement samples. For this purpose, carbon dots were synthesized by the solvothermic method using ethanol from p-phenylenediamine as a precursor. The PC obtained was purified in a chromatographic column and characterized by transmission electron microscopy (TEM), Fourier Transform Infrared Absorption Spectroscopy (FTIR), X-ray Excited Photoelectron Spectroscopy (XPS), UV-Visible Spectroscopy (UV- VIS) as well as luminescence spectroscopy. The PC obtained showed intense emission in red color, presenting a quantum yield equal to 11.3%. The characterizations carried out allowed to relate the observed emission to the carbon point surface characteristics, such like the content of chemical species containing oxygen and the presence of groups such as COOH. The application of the material for the quantification of chromium(III) ions was feasible, with a linear response between 4 and 20 mg L1 of chromium(III) ions. The results of the statistical analysis, for a confidence level of 95 %, suggested that the proposed method does not present significant difference, when compared to the method by energy dispersion X-ray spectroscopy, for the determination of chromium(III) ions in chromium(III) picolinate supplement samples.